Social experiments and instrumental variables with duration outcomes - Jaap Abbring; Gerard van den Berg (Institute for Fiscal Studies (IFS), 2005)
This paper examines the empirical analysis of treatment effects on duration outcomes from data that contain instrumental variation. We focus on social experiments in which an intention to treat is randomized and compliance may be imperfect. We distinguish between cases where the treatment starts at the moment of randomization and cases where it starts at a later point in time. We derive exclusion restrictions under various informational and behavioral assumptions and we analyze identifiability under these restrictions. It turns out that randomization (and by implication, instrumental variation) by itself is often insufficient for inference on interesting effects, and needs to be augmented by a semi-parametric structure. We develop corresponding non- and semi-parametric tests and estimation methods.
Keywords: C14; C31; C41; J6; 330; event-history analysis; intention to treat; non-compliance; policy evaluation; selection.; Nichtparametrisches Verfahren; Theorie